DEVELOPMENT OF FINANCIAL LITERACY IN LATVIAN STUDENTS - Kiseļova, Rita; Mihno, Linda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The development of the information and communication technologies goes hand in hand with changes in the financial environment, development of the offering and opportunities, and an ever increasing necessity for financial education to develop and advance in the schooling sector. It is therefore essential for school curricula to include the acquisition of knowledge and skills which support the development of financial literacy in order to assure that students are able to take care of their financial wellbeing in the future. The main aim is to find out what financial skills Latvian students need to develop in order to improve their financial literacy.Based on research studies conducted by other researchers, the research study is being conducted to look for the necessary skills and knowledge which financial literacy comprises and which might assure financial wellbeing in the future regardless of the constant development of the financial environment. The data of the Financial Module of the year 2012 OECD PISA study, in their turn, are used to analyse the financial literacy of Latvian students at the age of 15 by finding out the knowledge and skills students in Latvia have with regard to finances. By calculating the percentage of students able to solve the tasks given to them, the research study analyses which tasks Latvian students find difficult and which ones are easy for them. The research study explains what knowledge and skills financial literacy comprises. The results show that Latvian students find analytical tasks difficult, i.e., tasks which require substantiation of their opinion, whereas they find it easier to deal with tasks where use of mathematical skills is sufficient.The possible reasons for the current situation are provided and suggestions for improving it are offered in the research study.